The comparison of the efficacy of four behavioural procedures' ability to reduce disruptive behaviour : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Coombe, Stephanie (Massey University, 1995)
This research focused on the comparison of four behavioural procedures and their effectiveness at reducing disruptive classroom behaviour. Subjects who participated in this research were males and females, aged seven to nine in two typical primary school classrooms, in Palmerston North. Their ethinicities included Caucasian, Maori, Indian, Pacific Island and Sri Lankan. The procedure the school currently used to reward and discipline the children was compared with response cost plus positive reinforcement, the chance to earn back lost time after a specified period of appropriate behaviour and the chance to earn back lost time after displaying appropriate behaviour for a longer period of time than was previously required. Results found that the children's disruptive behaviour decreased the most with the use of response cost plus positive reinforcement. However, due to reasons of acceptability to the teachers and students, this procedure was not continued. Instead, the more acceptable and less stringent earn back time procedures were used and compared. From this, it was found that the earn back time procedure which required the children to behave appropriately for longer was the most efficacious in reducing disruption. Overall, this research supported the efficacy of response cost plus positive reinforcement for reducing disruptive behaviour in the classroom, while earning back time (and having to display appropriate behaviour longer) was shown to be second most effective.
Keywords: Classroom management; School discipline; Problem children